Tracheal Lobular Capillary Haemangioma: A Rare Benign Cause of Recurrent Haemoptysis - Metesh Nalin Acharya; Konstantinos Kotidis; Mahmoud Loubani (Case Reports in Surgery)
Lobular capillary haemangioma (LCH), previously known as pyogenic granuloma, is a benign vascular lesion commonly found within the oral and nasal cavity. However, it is rarely encountered within the trachea, where presenting features include recurrent haemoptysis, cough, and wheeze. We here describe a case of a 7 mm tracheal LCH in a 56-year-old woman, which was successfully resected at interventional bronchoscopy using biopsy forceps. Clinicians should be aware of tracheal LCH in the differential diagnosis for recurrent haemoptysis.